Determination of kinetic parameters of the reaction of formation of the solid-phase adsorbents - Булавин, Виктор Иванович; Блинков, Николай Андреевич (Technology audit and production reserves, 2015)
Reaction order of crystalline hydrate formation is calculated in the article. This reaction often takes place during contact with water of a number of inorganic salts, at least – acids and alkalis. Sometimes – and organic substances, such as known hydrocarbon and methane hydrates. These processes are often unwanted, so hydrate inhibitors are used in the main pipelines. But the formation of crystalline hydrates is useful process too. Thus, their use allows to form crystals, and more importantly, to remove unwanted water. This ability is applied for gas drying as well as organic and inorganic liquids, even – removal of these unwanted water. New compound forms after removal of anhydrous salt water from. The theoretical experience show that the quality of some dehydration salts is very high. Certain inorganic salts may bind more water by weight than weigh yourself. They also have the ability to some extent to give the bound water and again become anhydrous salts. This ability makes it possible to use them several times with almost no losses. So, we have a problem how exactly the process of interaction of inorganic salt with water to form crystalline takes place. It is used the fact that lowering the temperature of the reaction is faster, and that on this basis we can calculate the activation energy. Establishment of the reaction order and activation energy calculation contributes to the proper conducting this reaction in an industrial environment.